The moral states we seek: conscientious corporate branding for the perplexed - Yasin Sahhar; Christoph Moss; Jörg Henseler (Journal of Brand Management, 2025)
Corporate brands are increasingly willing or expected to demonstrate a moral stance, but existing frameworks often simplify moral agency, failing to capture its complexity. Consequently, corporate brands struggle to engage morality in a way that resonates with diverse stakeholder perspectives. How can moral development inform the orchestration of conscientious corporate brands? This conceptual paper aims to make sense of conscientious corporate branding as the project of becoming worthy of moral consideration. It introduces a maturity model, illustrating how corporate brands may evolve conscience as an emergent axis throughout different layers by emphasizing the importance of relational dynamics and situational contexts. This approach enriches theoretical discourse on conscientious corporate branding and provides actionable insights for brand managers seeking to enhance moral identity formation. Ultimately, this paper advocates for a shift toward an assemblage view of conscientious corporate branding, empowering corporate brands to become collective agents in an ever-evolving moral landscape.
Keywords: 330; Conscientious corporate branding; Corporate moral agency; Moral maturity; Moral assemblage